Effect of Machining Parameters on Tool Wear and Hole Quality of AISI 316L Stainless Steel in Conventional Drilling - Sultan, A.; Sharif, S.; Kurniawan, Denni (2015)
© 2015 The Authors This paper focuses on the effect of drilling parameters on tool wear and hole quality in terms of diameter error, roundness, cylindricity, and surface roughness. In this work, the drilling was conducted using uncoated carbide tool with diameter of 4 ± 0.01 mm with point angle of 135° and helix angle of 30°. The drilling was done at different levels of spindle speed (18 and 30 mmin-1) and feed rate (0.03, 0.045 and 0.06 mmrev-1). Austenitic stainless steel AISI 316L was the workpiece material. Comparatives analysis was done on hole diameter, roundness, cylindricity, and surface roughness of the drilled holes by experimentation. From the result, the hole quality characteristics are mostly influenced by cutting speed and feed rate. An exception was for circularity error where a two tail t-test for circularity error indicates that cutting speed and feed rate give no significant influence on circularity error. As the cutting speed increases, the surface roughness decreases (1.09 µm). Contrary, when the feed rate increases, the surface roughness value increases as well. For cylindricity error, lower cutting speed and lower feed rate will give better result. In terms of diameter error, feed rate influences more than cutting speed. Minimum diameter error was achieved when low cutting speed and low feed rate were employed.